Effects Of Glucono-delta Lactone (Gdl) Dipping And In-pack Pasteurization Treatment On Rice Starch Noodles Properties Upon Storage - Shamsudin, Nurul Athirah (Universiti Sains Malaysia, 2021)
Fresh laksa noodles have a short shelf life (2-3 days) due to short chain molecules of rice starch that easily retrograde. Glucono-delta lactone (GDL) is a weak acid that dissolves readily in water. Previous research found that GDL dipping followed by in pack pasteurization treatment was able to retain its mechanical and handling properties. Hypothesized that, the surface starch molecules could have been partially hydrolyzed that facilitated the formation of the coating layer on the surface of the noodle strands, which helped to prevent moisture loss during storage of laksa noodles. Hence, this study has been conducted to study the effects of GDL dipping and in-pack pasteurization treatment on rice starch noodles properties upon storage to support the hypothesis. Commercial rice starch noodles were dipped into the prepared GDL solution of different concentrations (0%, 0.05%, 0.10%, 0.5%, 1.0% and 1.5% w/v) for 2 mins before vacuum packed (150g/pack) and pasteurized at 85°C for 10 mins using a water bath.